Mystery still unresolved: Untouched "Blue heart" presenting at 40yrs of age - Sanjeev H Naganur; Ashish Tiwari; C R Pruthvi (Wolters Kluwer Medknow Publications, 2020)
The modern-day surgical techniques and strategies have changed the outlook of patients with dextro-transposition of great arteries (d-TGA). The survival of an unrepaired d-TGA into late adulthood is difficult to explain. Even when large intracardiac shunts are present, it still remains a lethal cyanotic congenital heart disease if it is not surgically corrected soon after birth. Here, we report an extremely rare case of d-TGA presenting at 40 years of age, with moderately elevated pulmonary artery pressures and relatively stable symptoms.